The most common founder pathogenic variant c.868G > A (p.Val290Met) in the NPHS2 gene in a representative adult Czech cohort with focal segmental glomerulosclerosis is associated with a milder disease and its underdiagnosis in childhood - Thomasová, Dana; Zelinová, Michaela; Libik, Malgorzata; Geryk, Jan; Votýpka, Pavel; Rajnochová Bloudíčková, Silvie; Krejčí, Karel; Reiterová, Jana; Jančová, Eva; Machová, Jana; Kollárová, Martina; Rychík, Ivan; et al. (Frontiers in Medicine, 2023)
Background: Genetic focal segmental glomerulosclerosis (FSGS) is caused by pathogenic variants in a broad spectrum of genes that have a variable representation based on subjects´ ethnicity and/or age.The most frequently mutated autosomal recessive gene in FSGS is NPHS2. Here we analysed the spectrum of NPHS2 variants and their associated phenotype in Czech adult FSGS patients.: A representative cohort of 234 unrelated adult patients with FSGS, derived from 225 families originating from all regions of Czechia, was analysed by massively parallel sequencing. In this study, we focused on the comprehensive analysis of the NPHS2 gene. The histological classification of FSGS followed the Columbia classification. Results: We detected seven (3%) cases bearing homozygous or compound heterozygous pathogenic NPHS2 variants. A single pathogenic variant c.868G>A (p.Val290Met) was found in the majority of NPHS2-positive cases (86%; 6 out of 7) in histologically confirmed instances of FSGS. Its allele frequency among unrelated NPHS2-associated FSGS patients was 50% (6/12) and was predicted by haplotype analysis to have arisen due to a founder effect. There is an identical V290M-related haplotype on all V290M alleles spanning a 0,7 Mb region flanking NPHS2 in Central European FSGS populations. The phenotype of the p.Val290Met NPHS2-associated FSGS demonstrated later onset and a much milder course of the disease compared to other NPHS2 pathogenic variants associated with FSGS. The mean age of the FSGS diagnosis based on kidney biopsy evaluation was 31.2 ± 7.46 years. The first disease manifestation of proteinuria was in 50% of all cases only in adulthood and 83% of them did not present with oedemas. One-third (33%) of studied subjects progressed to ESRD (2 out of 6) at the mean age of 35.0 ± 2.82 years. Conclusions: We identified the most prevalent pathogenic variant p.Val290Met in the NPHS2 gene in Czech adult FSGS patients which has arisen due to a founder effect in Central Europe. The documented milder course of the disease associated with this variant leads to the underdiagnosis in childhood. We established the histopathological features of the NPHS2-associated adult FSGS cases based on the Columbia classification. This might improve patient stratification and optimise their treatment.